Eternal Life as an Exclusively Present Possession: Perspectives from Theology and the Philosophy of Time. - Burley, Mikel (Sophia, 2016)
Does it make sense to think of eternal life not as an unending continuation of life subsequent to death but as fully actualized in one's present mortal and finite life? After outlining conceptual and moral reasons for being troubled by the notion of an endless life, this article draws upon the thought of major Christian theologians and philosophers of religion to expound the idea of eternal life as a possession exclusively of the life one is presently living. Supplementing the claims of religious thinkers with notions of four-dimensionalism and eternalism from theoretical physics and the philosophy of time, and considering important objections to the conception of eternal life in question, I argue for both the conception's intelligibility and its ethical and spiritual profundity.